2018
DOI: 10.1002/anie.201711439
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular (4+3) Cycloadditions of Pyrroles and Application to the Synthesis of the Core of Class II Galbulimima Alkaloids

Abstract: The first intramolecular (4+3) cycloaddition of pyrroles with epoxy enolsilanes as the electrophiles was developed and used to generate optically-enriched cycloadducts containing the nortropane substructure in good yields. Using this pyrrole cycloaddition as the key step, we achieved the asymmetric synthesis of a nortropane compound bearing the BCDEF ring structure common to the Class II galbulimima alkaloids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Very recently, Chiu et al. have just reported first intramolecular [4+3] cycloaddition reaction of pyrroles by using epoxy enolsilanes as a source of the oxyallyl cation . On the other hand, we have recently found that N ‐nosyl pyrrole is an efficient four‐carbon unit for [4+3] cycloaddition reaction, and the reaction with 2‐(silyloxy)‐acrolein 2 a as a three‐carbon unit is smoothly catalyzed by Cu(OTf) 2 or Sc(OTf) 3 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, Chiu et al. have just reported first intramolecular [4+3] cycloaddition reaction of pyrroles by using epoxy enolsilanes as a source of the oxyallyl cation . On the other hand, we have recently found that N ‐nosyl pyrrole is an efficient four‐carbon unit for [4+3] cycloaddition reaction, and the reaction with 2‐(silyloxy)‐acrolein 2 a as a three‐carbon unit is smoothly catalyzed by Cu(OTf) 2 or Sc(OTf) 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Very recently,C hiu et al have just reported first intramolecular [4+ +3] cycloaddition reactiono fp yrroles by using epoxy enolsilanes as as ource of the oxyallyl cation. [7] On the other hand, we have recently found that N-nosyl pyrrole is an efficient four-carbon unit for [4+ +3] cycloaddition reaction, [8] and the reactionw ith 2-(silyloxy)-acrolein 2a as a three-carbon unit is smoothly catalyzed by Cu(OTf) 2 or Sc(OTf) 3 . [9,10] Therefore, we expected that an intramolecular [4+ +3] cycloaddition would be possible by the generation of an oxyallyl cation from somep recursor possessing both N-nosyl pyrrole and 2-(silyloxy)-acrolein units as shown by A in Scheme1.Furthermore, since the preparation of such aprecursor might be troublesome due to the high reactivity of pyrroles, we planned to generate an oxyallylc ation in situ by the condensation of the aldehyde of 2-(silyloxy)-acrolein with nucleophiles such as hydroxyl, amino,a nd thiol groups that are tethered by the N-nosyl pyrrole.…”
mentioning
confidence: 99%
“…A related [4+3] cycloaddition involves the generation of 2-oxyallyl cations and their subsequent cycloaddition with dienes. Chiu 54 utilized an intramolecular cylcloaddition between pyrroles and epoxy enolsilanes to access the sevenmembered ring common to the core of Class II galbulimima alkaloids (Scheme 34). Treatment of pyrrole 175 with TESOTf followed by Et 3 N•3HF afforded the azatricycle 176 in 51% yield and good diastereoselectivity.…”
Section: Scheme 33 A) [4+3] Cycloaddition Of Diene and 3-oxidopyridinmentioning
confidence: 99%
“…While (4+3) cycloaddition did not proceed intermolecularly with pyrroles, the intramolecular reaction generated bicyclic alkaloids with embedded nortropane frameworks efficiently (Scheme 25). 70 Interestingly, pyrroles bearing a wide range of N-protecting groups, from very electrondonating to highly electron-withdrawing, all underwent effective and diastereoselective cycloadditions. This reaction reliably provided optically enriched aza-polycyclic products from enantiomerically pure epoxy enolsilanes and…”
Section: Scheme 24 Intramolecular Aza-(4+3) Cycloaddition Of Tetheredmentioning
confidence: 99%